Fatigue Behaviour Of Oil Palm Fruit Bunch Fibre/Epoxy And Carbon Fibre/Epoxy Composites - Kalam, Anizah (2003)
Tensile test on unidirectional Oil Palm Fruit Bunch (OPFB) fibre/epoxy composite and unidirectional Carbon Fibre (CF)/epoxy composite were conducted to determine their ultimate tensile stress, the Young's modulus and elongation at fracture Two different fibre volume fractions of 35'1"0 and 55% were studied in OPFB fibre/epoxy composite. The fibre volume fraction of CF/epoxy composite studied was 42%. The ultimate tensile stress determined from the tensile tests were then used to determine the maximum stress levels, Smax of fatigue tests for CF and OPFB fibre/epoxy composites. Two parameters were studied in fatigue test, which were stress ratio, R (0.1 and 0.5) and fibre volume fraction, Vr (35% and 55%). All Fatigue tests were performed at constant stress amplitude, at an air-conditioned room temperature of 20°C and at a frequency of 20 Hz. Observation on fractured surface of tensile and fatigue tested specimens were also done.The ultimate tensile stress of CF/epoxy composite is 247.0 MPa. OPFB fibre/epoxy composite with fibre volume fraction of 35% and 55% have ultimate tensile stress of 47.8 MPa and 46.1 Mpa, respectively. The observation on fractured surface of tensile tested specimens showed that CF and OPFB fibre/epoxy composites failed in a brittle manner. Fatigue behaviour of CF/epoxy composite shows a reduction in fatigue resistance with decreasing stress ratio. Three specimens survived 1 million cycles, which were cycled at stress ratio of 0.1 and maximum stress leveL Smax of 0.65. There was no indication of fatigue limit shown by S-N curves for OPFB fibre/epoxy composite for both fibre volume fractions. However the S-N curves of OPFB fibre/epoxy composite showed a decrease of fatigue resistance with the increase of fibre volume fraction from 35% to 55%. Two types of fractured surface were observed on the CF/epoxy composite failed in fatigue test, which were brittle and delamination. Meanwhile the fractured surface of OPFB fibre/epoxy composite showed brittle, delamination and fibre pull-out.